Effect of Project-Based Learning and Science Literacy Ability on Critical Thinking Skills in Virtual Learning of the Thermodynamics Course - Fenno Farcis; Gunarjo Suryanto Budi; Enny Wijayanti (Universitas Negeri Surabaya, 2022)
Research aims to find the effect of project-based Learning and scientific literacy skills on students' critical thinking skills 20 students in virtual learning of the Thermodynamics class at the Physics Education Study Program. The research design used the three-variable regression technique, which consists of two independent variables, namely project-based Learning (X1), the scientific literacy ability (X2), and the dependent variable, namely critical thinking skills (Y). Data collection techniques include observation sheets, questionnaires with a Likert scale, and evaluation of critical thinking skills. The results of the data analysis show that there is no partial effect of project-based learning on students' critical thinking skills, and the scientific literacy ability variable partially affects the critical thinking skills variable. Project-based Learning and scientific literacy skills significantly affect critical thinking skills. This research implies that there is evidence that Thermodynamics learning is not enough to apply project-based learning but must be equipped with literacy learning because, with a combination of these two things, students' critical thinking skills can increase significantly.